2022
DOI: 10.1007/s10826-022-02316-y
|View full text |Cite
|
Sign up to set email alerts
|

The Process Linking Child-Invested Contingent Self-Esteem and Conditional Regard: The Roles of Maternal Anger and its Regulation

Abstract: Parents whose self-esteem is contingent on their children’s achievements tend to exert more control over their children by displaying decreased affection and regard after failure in school (parental academic conditional negative regard). The current study examined parental anger and dysregulated anger expression as possible mechanisms in the respective association. In total, 221 mothers reported their child-invested contingent self-esteem, habitual dysregulated anger expression, anticipated anger after child f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In line with well-known socialisation theories (e.g., attachment theory and sociometer theory ), it is conceivable that parents influence their children’s SE via PACR. At the same time, there are also well-founded theoretical considerations that parents react with conditional regard to their children’s contingent SE [ 32 ] or use PACR because their own SE is contingent on their children’s performance [ 109 ]. Consequently, it can be concluded that increased PACR is related to low-insecure rather than optimal-secure SE.…”
Section: Discussionmentioning
confidence: 99%
“…In line with well-known socialisation theories (e.g., attachment theory and sociometer theory ), it is conceivable that parents influence their children’s SE via PACR. At the same time, there are also well-founded theoretical considerations that parents react with conditional regard to their children’s contingent SE [ 32 ] or use PACR because their own SE is contingent on their children’s performance [ 109 ]. Consequently, it can be concluded that increased PACR is related to low-insecure rather than optimal-secure SE.…”
Section: Discussionmentioning
confidence: 99%
“…For example, covariates might include intrapersonal characteristics such as children's big five personality characteristics or interpersonal factors such as grandparents' levels of conditional regard. The extent to which parents' self‐esteem is linked to their children's achievement can interact with parental conditional regard (Steffgen et al, 2022). Such parental characteristics and perceptions can be further explored in both longitudinal and experimental research.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when an individual's self-esteem is based on academic competence, one may act in a less supportive and caring way toward others, as they may be preoccupied with the promotion of their own self-worth (Park & Crocker, 2005). Indeed, research shows that parents' tendency to uphold their child-based self-worth is associated with their use of conditional regard (e.g., Otterpohl et al, 2020;Steffgen et al, 2022) and psychological control (e.g., Ng et al, 2014;Wuyts et al, 2015).…”
mentioning
confidence: 99%